AIAA Guidance, Navigation, and Control Conference and Exhibit 2005
DOI: 10.2514/6.2005-6143
|View full text |Cite
|
Sign up to set email alerts
|

Fast-Time Evaluations of Airborne Merging and Spacing in Terminal Arrival Operations

Abstract: NASA researchers are developing new airborne technologies and procedures to increase runway throughput at capacity-constrained airports by improving the precision of interarrival spacing at the runway threshold. In this new operational concept, pilots of equipped aircraft are cleared to adjust aircraft speed to achieve a designated spacing interval at the runway threshold, relative to a designated lead aircraft. A new airborne toolset, prototypes of which are being developed at the NASA Langley Research Center… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 5 publications
(6 reference statements)
0
9
0
Order By: Relevance
“…That study evaluated AMSTAR performance for typical step-descent arrival routes, which are approach methods commonly used today. The fast-time study demonstrated that AMSTAR and its onboard systems are highly robust to moderate variations in Automatic Dependent Surveillance-Broadcast (ADS-B) range, wind prediction errors, requiredtime-of-arrival metering errors, and merge frequency [5].…”
Section: Airborne Precision Spacingmentioning
confidence: 99%
See 1 more Smart Citation
“…That study evaluated AMSTAR performance for typical step-descent arrival routes, which are approach methods commonly used today. The fast-time study demonstrated that AMSTAR and its onboard systems are highly robust to moderate variations in Automatic Dependent Surveillance-Broadcast (ADS-B) range, wind prediction errors, requiredtime-of-arrival metering errors, and merge frequency [5].…”
Section: Airborne Precision Spacingmentioning
confidence: 99%
“…Runway throughput is increased with more accurate inter-aircraft spacing at the runway threshold, which can reduce excess spacing buffers between aircraft pairs [4][5][6]. However, as runways are expected to handle a higher volume of traffic, aircraft noise becomes a concern for residents living in areas surrounding 0-7803-9307-4/05/$20.00 ©2005 IEEE.…”
Section: Introductionmentioning
confidence: 99%
“…The behavior of a mix of spacing algorithms operating together also needs to be studied to determine if they produce a stable operation. st Digital Avionics Systems Conference October [14][15][16][17][18]2012 …”
Section: Discussionmentioning
confidence: 99%
“…For the assigned spacing interval the required wake turbulence separation criteria were converted 2C3-5 into time-based separations using the expected slowest final approach speeds based on wake category [12]. These numbers were then rounded upward approximately 10 seconds to add a safety buffer between spacing the aircraft and separating them.…”
Section: Overall Spacing Performancementioning
confidence: 99%